DOES TREATMENT STRATEGY FOR ATRIAL FIBRILLATION INFLUENCE MYOCARDIAL CONTRACTILE FUNCTION? - V. I. Podzolkov; A. I. Tarzimanova; I. J. Loriya; L. N. Mokhammadi (Столичная издательская компания, 2015)
Concept of deterioration of myocardial contractile function under long-term intake of antiarrhythmic drugs may be regarded as one of the myths of modern cardiology. Multiple references to negative influence of majority of antiarrhythmic drugs on myocardial inotropic function are speculative. Studies on estimation of influence of arrhythmia treatment strategy on myocardial contractile function are almost absent.Aim. To estimate dynamics of myocardial contractile function in patients with ischemic heart disease (IHD) and persistent atrial fibrillation (AF) compared among those treated with amiodarone 200 mg daily and with bisoprolol 5 mg daily.Material and methods. A total of 47 IHD patients with persistent AF were enrolled into the study. Sinus rhythm (SR) was restored during the first 24 hours of hospitalization in all the pa- tients. After SR restoration the patients were randomly allocated to two groups receiving either amiodarone 200 mg daily during 6 months for SR maintenance (group 1) or bisoprolol 5 mg daily for ventricular rate (VR) control (group 2). To estimate myocardial inotropic function all patients underwent steady-state radionuclide ventriculography (RVG) and echocardiography during the first 24 hours after SR restoration and 6 months later.Results. We revealed changes in left ventricle (LV) diastolic function, reduction of left atrium (LA) contribution to LV diastole and enlargement of LA anterior-posterior dimension during the first 24 hours after SR restoration in the patients of both groups.6-month SR maintenance in the first group of patients promoted significant decrease in isovolumic relaxation time (IVRT) from 103.4±1.01 ms to 96.4±1.1ms (р=0.02) and reduction of LA anterior-posterior dimension up to 36.1±3.8 mm (р=0.03). Target VR achievement in the second group of patients promoted restoration of LV diastolic function (decrease in IVRT from104.3±1.2 ms to 97.3±1.2 ms; р=0.03) but did not influence LA size (44.1±3.1 mm and 43.5±3.0 mm, respectively). Atrial inotropic function was only changed in the patients of group 1, the patients of group 2 did not reveal significant change in LA contribution to LV diastole.Conclusion. 6-month SR maintenance at amiodarone intake in IHD patients with persistent AF resulted in LA contraction, restoration of its contractility and improvement of LV diastolic parameters. Target VR for 6 months of bisoprolol intake led to LV diastolic function improvement, but did not influence LA dimension and contractile function.